Mimicking biological phenomena in hydrogel-based biomaterials to promote dynamic cellular responses. Issue 40 (14th September 2015) - Murphy, Nicholas P.; Lampe, Kyle J.
Abstract : Novel methods to endow cell-responsiveness into hydrogels are explored and successful work is summarized. Abstract : Hydrogel-based biomaterials, often classified as synthetic or natural, have long been pursued for cell culture, tissue engineering, regenerative medicine, and drug delivery. This classification system is now being blurred as hybrid partially synthetic systems using elements of native and designer molecules gain traction. Partially synthetic polymer gels can offer protection of encapsulated cells or drugs and provide instructional biochemical and/or biophysical cues to cells. To enable cellular interaction however, they must be endowed with bioactive elements. The extracellular matrix (ECM) provides a "toolbox" of bioactive moieties that can be incorporated into user-defined synthetic polymer scaffolds to promote cell responses such as migration or cell-derived material responses such as matrix multimerization. Incorporating bioactive elements like cell-adhesive peptides, protease-cleavable sites, and ECM-mimetic mechanical properties such as stiffness and porosity into robust well-characterized hydrogels has been pursued for decades. Through careful selection of linkage chemistries and structured design of material subunits, hydrogels have been created that facilitate a great deal of native cellular functions while retaining the customizable nature of engineered materials. A new thrust has emerged to engineer materials with the innate, dynamic bioresponsive activity of native ECM materials. This review characterizes the cell responsive units of native materials and the literature that has recently incorporated these elements into hydrogel tissue engineering and drug delivery materials to promote cell-controlled dynamic responses, a defining characteristic of native functional tissue.